John Duns Scotus: Questions on Aristotle’s Categories, qq. 1-3 - Salinas Leal, Héctor Hernando; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2016)
This is the first Spanish translation of the three first questions, of Scotus’s commentary on Aristotle’s Categories. The Franciscan distinguishes the subject matter of the Aristotelian treatise under the logical concept of «category», grounding the unity of their treatment as a scientific object on the unity of this concept. To do so, Scotus distinguishes the properly logic study of categories, from its linguistic treatment (which grounds in their utterance) and from the metaphysician’s study (where its real diversity is considered), al least in this first moment of his thought.